Identification of master regulator candidates in conjunction with network screening and inference - Saito, Shigeru; Zhou, Xinrong; Bae, Taejeong; Kim, Sunghoon; Horimoto, Katsuhisa (International journal of data mining and bioinformatics, 2013)
We developed a procedure for identifying transcriptional Master Regulators (MRs) related to special biological phenomena, such as diseases, in conjunction with network screening and inference. Network screening is a system for detecting activated transcriptional regulatory networks under particular conditions, based on the estimation of graph structure consistency with the measured data. Since network screening utilises the known Transcriptional Factor (TF)-gene relationships as the experimental evidence for molecular relationships, its performance depends on the ensemble of known TF networks used for its analysis. To compensate for its restrictions, a network inference method, the path consistency algorithm, is concomitantly utilised to identify MRs. The performance is illustrated by means of the known MRs in brain tumours that were computationally inferred and experimentally verified. As a result, the present procedure worked well for identifying MRs, in comparison to the previous computational selection for experimental verification.